(3GdebUhQ hGdeeOhOs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s
(3ChdgG (B:s
(3dGJQcff Edi Gdghi hGPcQ eaGQbI GdghGA Gdghi GdebUhO ghi GdfaS hGdghGA GdeeOhO eG Hjf GdSeGA hGdCQV s
(3BNQgG (B:s
(3jfJgi HHGH eG jVe Chdg ajbUQ hjaJM ajeO hGdeYfi eNJda s
(3HBNQgG fbhd cKjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1462s
(3eUOQ GbJfGA GdCUd (B:s
(3djOf s
Keywords: (3GdfMhs